2023
DOI: 10.1038/s41467-023-39770-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node targeted multi-epitope subunit vaccine promotes effective immunity to EBV in HLA-expressing mice

Abstract: The recent emergence of a causal link between Epstein-Barr virus (EBV) and multiple sclerosis has generated considerable interest in the development of an effective vaccine against EBV. Here we describe a vaccine formulation based on a lymph node targeting Amphiphile vaccine adjuvant, Amphiphile-CpG, admixed with EBV gp350 glycoprotein and an engineered EBV polyepitope protein that includes 20 CD8+ T cell epitopes from EBV latent and lytic antigens. Potent gp350-specific IgG responses are induced in mice with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Next, to explore anticancer activity of anti-CD19 autologous CAR T and allogeneic CAR NK cells in vivo, we implanted lymphoblastoid tumor cells (LCL) subcutaneously into NSG mice [ 35 37 ], modeling human B cell lymphoma therapy with either autologous CAR T cells [ 38 ] or allogeneic CAR NK cells [ 11 ]. Mice were treated with adoptive cell transfer (ACT) three days after tumor engraftment and injection of IL-2 to support transferred cells.…”
Section: Resultsmentioning
confidence: 99%
“…Next, to explore anticancer activity of anti-CD19 autologous CAR T and allogeneic CAR NK cells in vivo, we implanted lymphoblastoid tumor cells (LCL) subcutaneously into NSG mice [ 35 37 ], modeling human B cell lymphoma therapy with either autologous CAR T cells [ 38 ] or allogeneic CAR NK cells [ 11 ]. Mice were treated with adoptive cell transfer (ACT) three days after tumor engraftment and injection of IL-2 to support transferred cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, multi-epitope vaccines targeting Epstein–Barr virus (EBV) and influenza virus successfully elicit robust neutralizing antibodies and T-cell responses. The EBV polyepitope vaccine, which includes 20 CD8 + T-cell epitopes, induces high frequencies of CD4 + T cells and CD8 + T cells, which are maintained for more than 7 months ( Dasari et al, 2023 ). It has been reported that the norovirus (NoV) P particle, a 24-self-assembly of the protruding domain, displays H16, M2e, and NP9 on its surface, which elicit long-lasting hemagglutinin (HA)-specific neutralizing antibodies, M2e-CD4 + and CD8 + T-cell responses, and a nucleoprotein-specific CTL response, respectively ( Nie et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, EBV vaccination to stimulate endogenous TCRs has been advocated as a means to boost CAR armored EBVST expansion and function in patients ( 41, 42 ). This approach has been bolstered by recent strides in EBV vaccine delivery that have enabled effective and durable induction of EBV-specific T-cell responses ( 43 ).…”
Section: Discussionmentioning
confidence: 99%